Improving Inclusive Services in Educational Units Focusing on Children with Special Needs in Bontang City - Okto Arbianta Hutahaean; Aji Ratna Kusuma; Santi Rande; Estefanie R. Cortez (Universitas Muhammadiyah Makassar, 2026)
This study investigates the improvement of inclusive education services for children with special needs in Bontang City, Indonesia, with emphasis on teacher capacity, adaptive curriculum implementation, disability-friendly infrastructure, and stakeholder collaboration. A descriptive qualitative design was applied to examine how inclusive education policies are translated into service practices at the local level. Data were collected through observation, semi-structured interviews from the Education and Culture Office, inclusive schools, parents, and supporting institutions, and documentation of relevant policy and school records. The data were analyzed using qualitative procedures involving data reduction, data display, thematic coding, and conclusion drawing. The findings indicate that technical guidance and teacher training were perceived to improve teachers’ readiness to identify student needs and apply differentiated instruction. Curriculum adaptation was reflected in modified learning indicators, lesson plans, assessment criteria, and individualized support based on psychological assessment. Infrastructure development was demonstrated through the Autism Service Center, school accessibility facilities, and assistive learning resources, although distribution across schools remained uneven. Stakeholder collaboration involved local government, schools, parents, psychologists, and community organizations. The study contributes a locally grounded framework for strengthening inclusive education services through integrated pedagogical, institutional, infrastructural, and collaborative strategies.